2016
DOI: 10.18632/oncotarget.8774
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of developmental therapeutics for adrenocortical carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare disease with an estimated incidence of only 0.7 new cases per million per year. Approximately 30-70% of the patients present with advanced disease with very poor prognosis and without effective therapeutic options. In the recent years, unprecedented progresses in cancer biology and genomics have fostered the development of numerous targeted therapies for various malignancies. Immunotherapy has also transformed the treatment landscape of malignancies such as melanoma, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 145 publications
(157 reference statements)
0
20
0
Order By: Relevance
“…As a problem with the development of parthenogenetic embryos, research reports have shown that in the early embryonic development, the process of cell metabolism and apoptosis in the cytoplasm decay and nucleic acid differentiation is increased, thereby inhibiting the development of cells (Zhao et al, 2009;Diao et al, 2013aDiao et al, , 2013bCosta et al, 2016). Especially, the cause of this action can be seen as the main factor in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a problem with the development of parthenogenetic embryos, research reports have shown that in the early embryonic development, the process of cell metabolism and apoptosis in the cytoplasm decay and nucleic acid differentiation is increased, thereby inhibiting the development of cells (Zhao et al, 2009;Diao et al, 2013aDiao et al, , 2013bCosta et al, 2016). Especially, the cause of this action can be seen as the main factor in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…lems in the remodeling of the nuclear membrane during nuclear fission, which appears as a nuclear decay or increases the programmed cell death (Hajjari and Jahani, 2014;Costa et al, 2016;Park et al, 2016). The process of apoptosis is very important in embryonic development.…”
mentioning
confidence: 99%
“…Many studies have reported different expression levels of IGF1 and IGF2 in ACC compared to adrenocortical adenomas (ACA) . IGF2 expression is low or absent in the beginning of oncogenesis, which may suggest that other signalling pathways may also play a role in ACC tumorigenesis …”
Section: Introductionmentioning
confidence: 99%
“…In malignant tumors of adrenal glands, adrenocortical carcinoma (ACC) is an exceedingly rare disease caused by a cancerous growth within the cortex. ACC has the estimated incidence of 0.7 cases per million per year in the United States and lead to 0.2% of all cancer deaths [4,5]. ACC may occur in adults or children with a female to male ratio of 1.5 -2.5:1 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…ACC has the estimated incidence of 0.7 cases per million per year in the United States and lead to 0.2% of all cancer deaths [4,5]. ACC may occur in adults or children with a female to male ratio of 1.5 -2.5:1 [5,6]. Many ACCs are asympomatic and nonfunctional as adrenal incidentalomas.…”
Section: Introductionmentioning
confidence: 99%